Seeing Potential - Lindsay Fox (SAGE Publishing, 2015)
I present new evidence on the effects of having a same-sex or same-race teacher on two salient outcomes: teacher expectations for postsecondary attainment and teacher recommendations for advanced courses. My identification strategy conditions on all subject-invariant student traits to provide causal estimates of the effects using data from the Educational Longitudinal Study of 2002. Across the full sample, there is little evidence of an effect of having a same-sex or a same-race teacher on expectations or recommendations. However, I find surprisingly large effects for Black students on teacher expectations. For these students, the effect of a same-race teacher on teacher expectations to complete more than high school is between 11 and 17 percentage points. This effect is at least 70% of the White-Black race gap in teacher expectations.